ENGLISH-AN ANALYIS OF THE CONCEPT OF ONENESS FROM A SUFI PERSPECTIVE AS PRESENTED BY MUHAMMAD NAFIS AL-BANJARI IN HIS TREATISE - AL-DURR AL-NAFIS - Muhammad Khairi (دی اسکالر)
The teachings of Tasawuf have flourished in the Malay world due to the efforts from Malay scholars who studied in Makkah. Muhammad Nafis al-Banjari is one of them. He wrote his treatise on tawhid in a small epistle known as al-durr al-nafis fi bayan wahid al-afcal- wa al-asma’ wa al-sifat wa al-dhat al-taqdis . His teaching of tawhid written in Malay Jawi script is embroidered with Sufi teachings. However, his teachings raise issues of controversial and misunderstood nature. One of the contentious issues his epistle is blamed for is regarding the promotion of pantheism having connotation of unity of being (wahdah al-wujud). The objective of this study is to reveal the misconception of tawhid embroidered in the Sufi teachings and the importance of understanding the correct concept of tawhid from the original sources of Islam. This paper employs a detailed historical and textual study.  Despite various controversies, al-Banjari epistle is considered to be a valuable work from a historical point of view. His highly succinct explanation requires additional reference and commentaries for readers to acquire appropriate understanding. It is according considered necessary to study his epistle under the proper guidance from the learned shuyookh to conceive it correctly.